2018
DOI: 10.18378/rvads.v12i5.4756
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química de polpas de manga ‘Rosa’ liofilizadas

Abstract: Objetivou-se neste estudo realizar a caracterização físico-química de polpa de manga ‘Rosa’ em pó, obtida por liofilização. Utilizou-se polpa integral e uma formulação contendo 30% de maltodextrina (agente de secagem). As amostras foram homogeneizadas e congeladas a -18ºC para posterior liofilização por um período de 72 horas. Realizou-se análises das polpas (integral e formulada) e dos pós obtidos quanto aos parâmetros de umidade, atividade de água, sólidos solúveis totais, pH, acidez total titulável, ácido a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The whole pulp of cactus pear showed values of 89.97% (wet basis) and 13.03 for water content and total solids, respectively; thus, these values were similar to those established by Oliveira et al (2007) for the pulp of branches of 'mandacaru' (Cereus jamacaru), 88.36% (wet basis) and 6.66.…”
Section: Resultssupporting
confidence: 82%
“…The whole pulp of cactus pear showed values of 89.97% (wet basis) and 13.03 for water content and total solids, respectively; thus, these values were similar to those established by Oliveira et al (2007) for the pulp of branches of 'mandacaru' (Cereus jamacaru), 88.36% (wet basis) and 6.66.…”
Section: Resultssupporting
confidence: 82%
“…In the assessment carried out by Barros et al (2013) when analyzing the physicochemical properties of soybean oil, a moisture content of 0.1 to 0.2% was obtained. Similarly, Almeida et al (2013) in their research entitled physical-chemical characterization of mixtures of vegetable oils for food purposes, they obtained moisture content around 0.2%, results consistent with those verified in sample A of the present study. Ahmed et al (2019) developing their study on evaluation of the quality and level of vitamin A fortification of soybean oil available in Bangladesh, obtained, similarly, moisture content ranging from 0.35±0.02 to 0.46±0.04%, Gariso (2011) obtained a moisture content around 0.46%, when developing his study on the effect of successive reuses of frying oils on quality parameters, results allied to those obtained in samples B and C of the present study.…”
Section: Moisture Contentsupporting
confidence: 91%
“…Results allied to those obtained in the present research were reported in the study conducted by Silva et al (2012) with the aim of characterizing the physical-chemical and dielectric constituents of biodegradable oils that obtained acid level around 0.14 mg/KOH for sunflower oil and 0.2 mg/KOH for soybean oil. Similarly, Almeida et al (2013) when evaluating the physical-chemical characterization of mixtures vegetable oils for food purposes, obtained acid index of 0.17mg/KOH. In agreement with the results of the present study, Filho et al (2014), in their study on the deterioration of vegetable oils exposed to different storage conditions, observed that soybean oil had acidity around 0.20KOH m/m to 0.26KOH m/m.…”
Section: Acidity Levelmentioning
confidence: 98%